Hubungan Kondisi Lingkungan Rumah dan Perilaku Keluarga dengan Kejadian Demam Berdarah Dengue Di Kabupaten Aceh Besar - Sofia, Sofia; Suhartono, Suhartono; Wahyuningsih, Nur Endah (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2014)
Background: Dengue Hemorrhagic Fever (DHF) is a communicable disease caused by dengue virus known as the most spread disease in the world. In Aceh Besar district, DHF cases were found annually, 156 cases was recorded in 2013 (IR=42,0 per100.000 people), 1 case of death was reported (CFR=0,88%). It was seen that almost household had breeding places and used materials which can trun into breading places of Aedes aegypti. This research was to analyze the relationship of household environmental condition and family behavior to the incidence of DHF. Methods: This research was observational analytic study using case control design with total samples of 150 respondents, consisted of 75 cases and 75 control. Data analysis were using Chi-Square and Logistic Regression. Results: The result was that there was significant relationship between breeding place in household (p=0,000 and OR = 5,5), temperature in house (p=0,000 and OR= 4,0) and habits of cleaning up water container (p=0,000 and OR= 4,7) to the incidence of DHF. Conclusion: Community can prevent the cycle of DHF transmission by doing activities such as egg, larva, pupa eradication in its breading places, cleaning up water container at least, once in less then 7 days and actively perform 3 M Plus activities. Coordination between various stake holders is needed to observe sanitation of environment so then breeding places will not exist for Aedes aegypti. Keywords: Residence environment, family behavior, DHF